Proceedings of the International Conference on Arts and Design Education (ICADE 2018) 2019
DOI: 10.2991/icade-18.2019.59
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Dance Creativity on Executive Functions of Early Childhood

Abstract: The purpose of this study is to find out the influence of dance creativity on executive functions of early childhood. The research method used is a quasi-experimental design with paired data t-test analysis. This study was conducted on 50 respondents aged 5-6 years. The results showed that t hit > t table, sig <0.01 there was a significant difference between before and after the dance creativity activities implemented. Based on the result of this study, it can be concluded that dance creativity can significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Working memory as measured by the Digit Recall score was also enhanced after the aerobic dance program but not for participants in the control group. These findings are in line with previous reports that creative dance training significantly influenced EF in children (Yetti et al, 2019) and with findings that a street dance program significantly improved cognitive flexibility, inhibition and working memory in preschool children (Shen et al, 2020). Oppici et al (2020) gave support in their finding that dance practice coupled with a high cognitive challenge improved working memory in children.…”
Section: Discussionsupporting
confidence: 93%
“…Working memory as measured by the Digit Recall score was also enhanced after the aerobic dance program but not for participants in the control group. These findings are in line with previous reports that creative dance training significantly influenced EF in children (Yetti et al, 2019) and with findings that a street dance program significantly improved cognitive flexibility, inhibition and working memory in preschool children (Shen et al, 2020). Oppici et al (2020) gave support in their finding that dance practice coupled with a high cognitive challenge improved working memory in children.…”
Section: Discussionsupporting
confidence: 93%
“…Working memory as measured by the Digit span score was also enhanced after the motor activity program but not for participants in the control group. These findings are in line with previous reports that creative education in math classes training significantly influenced EF in children (Yetti et al, 2019). A very recent study has also reported that motricity improved inhibitory control and working memory in primary school children (Rudd et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…Dance includes a wide range of social behaviors [41] and constitutes a natural means of emotional expression [42]. It develops self-control, especially in reactions to feel-ings such as anger and fear [43]. Moreover, it provides a means to communicate and share feelings.…”
Section: Intervention With Robots In Art and Game Therapymentioning
confidence: 99%